The sexually transmitted diseases in the story «Los amantes de real orden» - Sandoval Roncales, Jennifer Paola (2022)
This article will analyses the story «Los amantes de real orden», a text that is part of the fourth series of Ricardo Palma,s Tradiciones peruanas (Peruvian Traditions). In this text, the main premise is that the human being is characterized by his constant search for pleasure, with sexual pleasure being one of the most important. In this work, we want to make known the sexually transmitted diseases that were spread during the viceroyalty of Peru because of the promiscuity that the citizens had as a way of life. It also aims to inform and raise awareness among young people in order to considerably reduce the risk of contracting sexually transmitted diseases.